Transition of graduate nurses from student to practice during the COVID-19 pandemic: Integrative review - Kholofelo L. Matlhaba; Sisinyana H. Khunou (Elsevier, 2022)
The COVID-19 pandemic has had dire consequences for all health care workers including nurses. Consequently, those graduate nurses who transitioned into practice during that time were not spared the pandemic's impact. The purpose of this integrative review is to identify and present the extant literature on the transition of graduate nurses from student to practice during the COVID-19 pandemic. Online data bases ranging from the Cumulative Index to the Nursing and Allied Health Literature, the Education Resources Information Centre and PsychINFO were all perused for publications between 2019 and 2021. Key search terms included COVID-19, graduate nurses, newly qualified nurses, transition. The researchers then carefully assessed the articles found and used the coder to determine the relevance of those selected articles. The Critical Appraisal Skills Programme was used to validate the quality of the research articles considered for review. The search of these data bases produced 10 articles which met the inclusion criteria.Four main themes emerged from the study, namely: Organisational challenges faced by graduate nurses during their transition into practice during the COVID-19 pandemic; Personal challenges experienced by graduate nurses in their transition into practice in the context of COVID-19 pandemic; Positive outcomes emanating from the transition of graduate nurses during the pandemic; and Factors which facilitated the transition from student to practice by graduate nurses during the pandemic.The organisational challenges findings revealed that graduate nurses experienced such problems as a shortage of resources, burnout syndrome, work overload and lack of support. Challenges related to their transition throughout the COVID-19 pandemic period included psychological effects and the theory practice gap. Positive outcomes that emerged were learning and better employment opportunities. Factors which could have better facilitated their transition encompassed the availability of equipment and training opportunities. Recommendations include increased collaborative efforts amongst stakeholders to support and mentor graduate nurses during such emergencies; and psychological interventions that could assist with coping in such dire situations as the COVID-19 pandemic.